Intracellular Chloride Channels: Novel Biomarkers in Diseases - Gururaja Rao, Shubha; Patel, Neel J.; Singh, Harpreet (Frontiers in Physiology, 2020)
Ion channels are integral membrane proteins present on the plasma membrane as well as the intracellular membranes. It had been long thought that transmembrane ion fluxes depend on conduction pathways located within a specific group of proteins given the lipid bilayer was characterized as impermeable to water-soluble ions. Only in the 1980s, convergence of state-of-the-art biophysical and molecular biological techniques allowed in-depth characterization and identification of specific proteins responsible for ion fluxes. In the human genome, there are more than 400 known genes encoding ion channels. On changing their conformation from closed to open states, they allow ions to flow through them albeit tightly regulating the ionic flux. Ion channels are known to regulate several cellular, organellar and physiological processes, and any mutation or disruption in their function can result in common (tumors) to rare pathological disorders. Ion channels present on the plasma membrane are widely acknowledged for their role in various biological processes but in recent years, several studies have pointed out the importance of intracellular ion channels. Intracellular ion channels are not well-understood in the context of pathological conditions such as oncochannelopathies or as therapeutic targets for cancer. A novel class of intracellular ion channels, Chloride Intracellular Ion Channels (CLICs), are mainly documented for their role in cardiovascular and neurophysiology, and tumor biology. They have been recently shown to be localized to mitochondria. In fact, CLIC5 is the first mitochondrial chloride channel identified up to the molecular level in the inner membrane, and CLIC4 is located in the predominantly in outer mitochondrial membranes. In this review, we have focused on this unique class of intracellular chloride channels, and their role in pathologies that include cardiovascular, cancer and neurodegenerative diseases.